Dying, dignity and diabetes. (2nd June 2021) - James, June
Abstract: In 2019, the International Diabetes Federation attributed 4.2 million deaths due to diabetes. 1 In the United States, diabetes was said to be the seventh leading cause of death in 2017; this information was based on over 83, 000 death certificates. 2 Over half a million people died in the United Kingdom 3 in 2017 and, in the same year, 117, 000 of these individuals had diabetes. 4 The cause of death in these individuals is not usually attributed to acute diabetes complications such as diabetic ketoacidosis (DKA), hyperosmolar hyperglycaemic state (HHS) or hypoglycaemia, but to the long‐term complications which occur in individuals living with the condition such as cardiovascular disease, chronic kidney disease and dementia or respiratory disease or cancer. A holistic approach to the care of people living with diabetes as they near the end of their lives is important if acute metabolic complications, unnecessary treatment regimens and excessive monitoring are to be avoided. 5 Individuals with diabetes will undoubtedly face additional psychological and clinical challenges as they enter end of life care. This article takes a practical approach to end of life care in people with diabetes; it includes national and international recommendations and simple algorithms developed to support health care professionals caring for these individuals. Copyright © 2021 John Wiley & Sons.